Lehčené podlahy na bázi pěnobetonů a plynobetonů s využitím druhotných surovin - Kapčuk, Pavel (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Tato diplomová práce se zabývá vývojem nové lehčené hmoty pro průmyslové podlahy založené na bázi pěnobetonu a neautoklávovaného pórobetonu s možným využitím druhotných plniv a přírodních lehčených plniv namísto klasického kameniva, které by bylo možné skladovat ve formě suché směsi připravené k použití jen s přidáním vody.

This thesis is oriented on development of new porous materials for industrial floors based foam concrete and not autoclaved aerated concrete with the possible use of secondary raw materials and natural lightweight aggregates instead of classic aggregates. The dry mixture should be stored in bags as ready to use with the addition only of water.
Lightweight floors based on aerated concrete and foam concrete with the use of secondary raw materials
Keywords: pěnobeton; plynobeton; druhotné suroviny; plynotvorná přísada; pěnotvorná přísada; foam concrete; aerated concrete; secondary raw materials; aerating additive; foaming additive